2014
DOI: 10.5812/numonthly.24308
|View full text |Cite
|
Sign up to set email alerts
|

Leiomyosarcoma of the Spermatic Cord in a Seventy-Five-Year-Old man

Abstract: Introduction:Leiomyosarcoma is a malignant soft tissue tumor that can arise from any tissue containing smooth muscle. Leiomyosarcomas of the spermatic cord are rare tumors of non-testicular origin, which drain into the retroperitoneal lymph nodes and have been reported in less than 150 cases in the literature until now. Radical inguinal orchiectomy and high ligation of the cord is the standard primary surgical procedure in spermatic cord leiomyosarcoma.Case Presentation:Here we reported a 75-year-old man who p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Intimate pathophysiologic mechanisms that lead to the occurrence of these neoplasms are unknown, although it is speculated with the role that could play an occasional degeneration of a leiomyoma originated prior from funicular structures constructed by smooth-muscle. 1 , 2 …”
Section: Discussionmentioning
confidence: 99%
“…Intimate pathophysiologic mechanisms that lead to the occurrence of these neoplasms are unknown, although it is speculated with the role that could play an occasional degeneration of a leiomyoma originated prior from funicular structures constructed by smooth-muscle. 1 , 2 …”
Section: Discussionmentioning
confidence: 99%
“…Only about 115 cases of spermatic cord leiomyosarcoma have been reported in the world literature, and only about 43 cases in the English literature. [4][5][6][7][8][9] Thus, the present case seems important, because the present case adds a case in the lists of spermatic cord leiomyosarcoma. Immunohistochemically, the present tumor was positive for vimentin, α-smooth muscle actin, h-caldesmon, desmin (focal), p53, and Ki-67 antigen (labeling = 34%), but negative for pancytokeratin AE1/3, pancytokeratin CAM5.2, KIT (CD117), CD34, S100 protein, and myoglobin.…”
Section: Discussionmentioning
confidence: 99%
“…The most recent study also reported that there are only about 115 cases of leiomyosarcoma of the spermatic cord in the world literature. [4][5][6][7] This pathological entity in spermatic cord was first reported by Wessel in 1953. [8] All of these reported cases of leiomyosarcoma in spermatic cord are case reports, and there have been no comprehensive studies using many cases.…”
Section: Introductionmentioning
confidence: 99%
“…LMS of the spermatic cord are uncommon neoplasia of non-testicular origin and generally arises in the sixth or seventh decade. Originally considered to be malignant smooth muscle tumors or leiomyosarcomas arise from embryologic undifferentiated mesenchymal cells of the cremasteric mucle or vas deferens cells [7] . Most paratesticular LMS are 2 to 9 cm in diameter [5] .…”
Section: Discussionmentioning
confidence: 99%